2010
DOI: 10.1039/b917316a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of diporphyrin sensitizers for dye-sensitized solar cells

Abstract: Novel porphyrin dimers with broad and strong absorption in the visible and/or near IR regions have been synthesized; the meso-meso-linked porphyrin dimer (YDD1) exhibited the best photovoltaic performance with power conversion efficiency 5.2% under AM 1.5G one solar illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 34 publications
1
63
0
1
Order By: Relevance
“…Table 1 summarizes recently published data for dimer sensitised solar cells. [22][23][24][25][26] As expected, using conjugated linkers results in the enhancement of the absorption spectrum, while it seems to result in the decrease of V oc . On the other hand, dimer sensitisers using nonconjugated linkers showed higher V oc than monomer sensitisers.…”
Section: Introductionsupporting
confidence: 67%
“…Table 1 summarizes recently published data for dimer sensitised solar cells. [22][23][24][25][26] As expected, using conjugated linkers results in the enhancement of the absorption spectrum, while it seems to result in the decrease of V oc . On the other hand, dimer sensitisers using nonconjugated linkers showed higher V oc than monomer sensitisers.…”
Section: Introductionsupporting
confidence: 67%
“…However, the absorption wavelength values of the porphyrin dye did not reach the near IR region and the existence of a gap between the Soret and Q bands in monomeric porphyrins limits their cell performance. The more successful way to overcome this limit is to connect more porphyrin dyes through their meso and beta peripheral positions [4]. Different approaches have been followed to reach this goal, such as for example the preparation of expanded porphyrinoids [5], where the aromatic system spans over a macrocycle larger than that of porphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…These dyad structures demonstrate remarkable absorbance values in solution with many reaching onsetso f8 00 nm with one reaching 1200 nm in solution and exhibiting e of 100 000 Lmol À1 cm À1 . Mai et al found that increasing interporphyrin interactions througha ne thynyl-linker red-shifts absorbance onsetsi ns olution and gives rise to ap anchromatic IPCE response up to 850 nm and PCEs up to 4.1 %( YDD0) [77] However,o wing to a stabilized excited-state energy level,e lectron injection was found to be problematic for YDD0. Wu et al synthesized an alkoxy-wrapped ethynyl-linked porphyrin dyad, which exhibited av ery broad IPCE response (onset at 900 nm) and ap eak value of 35 %( YDD6).…”
Section: Porphyrin-based Photosensitizersmentioning
confidence: 99%